2013
DOI: 10.1111/cid.12086
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Particulated Autogenous Bone on the Early Volume Stability of Maxillary Sinus Grafts with Biphasic Calcium Phosphate: A Randomized Clinical Trial

Abstract: An evident decrease of graft volume over the first 6 months of healing has to be expected irrespective of bone graft composite. Autogenous bone seems to have no evident impact on the volume decrease when added to BCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
24
0
3
Order By: Relevance
“…28,30,31 In the present study, all 52 dental implants were clinically successfully osseointegrated 4 months after their placement. Despite the fact that biomaterials are commonly added to autogenous bone for sinus grafting, 28,29,32 it was opted not to add another variable to this study.…”
Section: Discussionmentioning
confidence: 99%
“…28,30,31 In the present study, all 52 dental implants were clinically successfully osseointegrated 4 months after their placement. Despite the fact that biomaterials are commonly added to autogenous bone for sinus grafting, 28,29,32 it was opted not to add another variable to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been published on bone graft stability based on two‐dimensional imaging techniques, demonstrating a significant decrease in augmented bone height within 6‐24 months after sinus lifting . Studies have also been reported on the three‐dimensional (3D) volume stability of these grafts . Although being numerous, these studies differ substantially regarding follow‐up time, method of evaluation, bone graft material, and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…CT data were loaded into a validated computer application (Voxim; IVS Technology GmbH, Chemnitz, Germany) to determine and calculate the respective augmentation volumes as already described in another study (Kühl et al. ). The impression material in the sinus below the Schneiderian membrane was manually marked in three views (coronal, sagittal and transversal view), and the software automatically calculated the resulting volumes in millilitres (ml) (Fig.…”
Section: Methodsmentioning
confidence: 99%